Investigating the spatiotemporal non-stationary relationships between urban spatial form and land surface temperature: A case study of Wuhan, China. (September 2021) - Lu, Youpeng; Yue, Wenze; Liu, Yong; Huang, Yaping
Highlights: The relationships between USFs and LST vary significantly among different floor-area-ratio zones. USFs largely contribute to the variance of LST in summer and autumn compared with winter. Building morphology exerts more impact on LST in relatively highly intensive built-up zones. Urban heat island can be precisely mitigated by optimizing USFs considering the varied relationships between USFs and LST. Abstract: This article aims to examine the pathways of urban spatial forms in mitigating urban heat island (UHI) intensity across urban areas in different seasons. By investigating the case of Wuhan, we quantified urban spatial form (USF) factors concerning land use, land cover, and building-group morphology and the land surface temperatures (LST) in summer, autumn and winter of 2, 357 block units. The seasonal relationships between USF and LST are explored at the large scale of the whole study area and different zones of block units categorized by floor area ratio. The results suggest that relationships between USF and LST vary spatially and temporally. First, although most urban spatial form factors show significant correlations on LST at the global scale, the correlations vary significantly among low, medium, and high floor-area-ratio zones. Second, USFs largely contribute to the variance of LST in summer and autumn compared with winter. Third, building morphology exerts more impact on LST in relatively highly intensive built-up zones, while land use and land cover factors have more impact in low-intensity areas. Lastly, UHI can be precisely mitigated by optimizing USFs considering the varied relationships between USFs and LST. This study theoretically deepens the understanding of the variation of the relationships between built-up urban areas and UHI at the scale of the basic planning regulation units, which is conducive to formulating down-to-earth regulation measures to cool cities and communities.